Keragaman Jenis Belalang (Orthoptera) di Persawahan Desa Beringin Kencana Kecamatan Tabunganen - Meidita Alpisah Rina; Aulia Ajizah; Riya Irianti (Wahana-Bio: Jurnal Biologi dan Pembelajarannya, 2021)
Grasshoppers act as pests and act as predators, scavengers, and decomposers of organic matter. In maintaining the ecosystem of rice fields, grasshoppers have a very important role in maintaining their balance. The purpose of this study was to describe the diversity of grasshoppers (Orthoptera) in the rice fields of Beringin Kencana Village, Tabunganen District. The research methods used is a descriptive method with sampling using roaming techniques with line transect methods. The results obtained 9 species of grasshoppers, namely Oxya chinensis, Mantis religiosa, Gesonula mundata, Conocephalus fasciatus, Conocephalus discolor, Phlaeoba fomusa, Aiopolus thalassinus, Acrida conica, and Scudderia furcata. The grasshopper diversity index is 1.83 including the medium diversity category.